Sociology for education studies : connecting theory, settings and everyday experiences - Simon, Catherine A.; Downes, Graham (Abingdon, Oxon ; New York, NY : Routledge, 2020)
'Sociology for Education Studies provides a fresh look at the sociology of education, focussing on themes such as habitus, hegemony and intersectionality. It supports students in applying sociological theory to their own educational experiences and developing an understanding of why social orders appear to be predetermined, why the state continues to create education policy in certain forms and, crucially, how to make it better'--
Includes bibliographical references and index.
Keywords: Education -- Sociological aspects